2011
DOI: 10.1089/dia.2011.0041
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescence Method for Measurement of Glucose Transport in Kidney Cells

Abstract: Background: Diabetes may alter renal glucose reabsorption by sodium (Na + )-dependent glucose transporters (SGLTs). Radiolabeled substrates are commonly used for in vitro measurements of SGLT activity in kidney cells. We optimized a method to measure glucose uptake using a fluorescent substrate, 2-(N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino)-2-deoxyglucose (2-NBDG). Methods: Uptake buffers for 2-NBDG were the same as for 14 C-labeled a-methyl-d-glucopyranoside ([ 14 C]AMG). Cell lysis buffer was optimized for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 34 publications
6
66
1
1
Order By: Relevance
“…We observed the cellular uptake of 2-NBDG in the proximal tubule was similar from the apical and basolateral side of the cell, suggesting uptake by both SGLT and the glucose transporter (GLUT) as observed in studies in isolated cells (2,7,23,33).…”
Section: D)supporting
confidence: 70%
See 1 more Smart Citation
“…We observed the cellular uptake of 2-NBDG in the proximal tubule was similar from the apical and basolateral side of the cell, suggesting uptake by both SGLT and the glucose transporter (GLUT) as observed in studies in isolated cells (2,7,23,33).…”
Section: D)supporting
confidence: 70%
“…In this study, we employed positron emission tomography (PET) and intravital multiphoton microscopy (MPM) to assess cortical and proximal tubule glucose tracer uptake, respectively, following experimental perturbations of kidney metabolism. Applying dynamic image acquisition PET with [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] fluoro-2-deoxyglucose ( 18 F-FDG) and tracer kinetic modeling, we found that an intracellular compartment in the cortex of the kidney could be distinguished from the blood and urine compartments in animals. Given emerging literature that the tumor suppressor protein p53 is an important regulator of cellular metabolism, we demonstrated that PET imaging was able to discern a threefold increase in cortical 18 F-FDG uptake following the pharmacological inhibition of p53 in animals.…”
mentioning
confidence: 99%
“…Lipolysis and glucose uptake assays in 3T3-L1 cells Lipolysis and glucose uptake assays were performed as previously described in fully differentiated 3T3-L1 adipocytes (54,56). See the Supplemental Methods for additional details.…”
Section: Transient Transfection Of 3t3-l1 Cellsmentioning
confidence: 99%
“…Time and dosedependent uptake of glucose was measured after incubation of cells with 100, 200, or 500 mM of the fluorescent substrate 2-(N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino)-2-deoxyglucose (2-NBDG) over the course of 120 min in 96-well plates. 41 Competitive inhibition of SGLT activity was determined in transwell plates after incubation with 250 mM 2-NBDG for 1 h in the presence or absence of 1000 mM phlorizin (SGLT inhibitor) in Na+ and Na+ free buffers. Inhibition of Na+-independent, facilitative transporter activity (GLUT) was shown after pretreatment of HPTECs for 10 min with 50 mM cytochalasin B (SGLT inhibitor) followed by 1 h incubation with 250 mM 2-NBDG in Na+ and Na+ free buffers.…”
Section: Transport Activity and Enzymatic Assaysmentioning
confidence: 99%